Trends in Diagnostic Flexible Laryngoscopy and Videolaryngostroboscopy Utilization in the US Medicare Population - Itamura, Kyohei (JAMA Otolaryngol Head Neck Surg, 2019)
IMPORTANCE: Diagnostic flexible laryngoscopy (DFL) is the second-most reimbursed procedure by Medicare in otolaryngology. However, the economic trends of this procedure on a population level are unknown. OBJECTIVE: To describe national- and state-level DFL and videolaryngostroboscopy (VLS) utilization and payment trends from 2000 to 2016 in the Medicare population. DESIGN, SETTING, AND PARTICIPANTS: This population-based, cross-sectional study of all Medicare beneficiaries from 2000 through 2016 found that at the national level the total absolute number of DFLs performed in the US Medicare population increased by 87% from 344 183 to 645 172 services, whereas total absolute payments for DFLs made by Medicare concurrently increased by 41% from $38 720 243 to $54 499 071. Rates of DLS and VLS categorized as Current Procedural Terminology (CPT) code 31575 and 31579, respectively. Analysis was carried out between November 18, 2018 and December 18, 2018. EXPOSURES: Diagnostic flexible laryngoscopy and VLS. MAIN OUTCOMES AND MEASURES: The DFL and VLS utilization rates, payments, and reimbursement rate trends were analyzed by year and state. Utilization was assessed for physician characteristics, including specialty and credentials. RESULTS: Nationally from 2000 to 2016 in the Medicare population, DFL utilization per Medicare enrollee increased 30% from 0.0087 to 0.0110 and payment per enrollee decreased 2% from $0.98 to $0.96, whereas VLS utilization and payment per enrollee both increased at least 300% during the same time period, with VLS procedure per enrollee and payment per enrollee increasing by 382% from 0.00028 to 0.0013 and 301% from $0.05 to $0.22, respectively. There was a weak correlation between reimbursement and utilization per enrollee for both DFL (r = 0.23; 95% CI, 0.12-0.34) and VLS (r = 0.26; 95% CI, 0.14-0.37) performed from 2012 to 2016. In 2016, the mean (SD) payment per DFL was $85.14 ($7.95), ranging from $65.45 in Puerto Rico to $104.82 in Washington, DC, a 1.6-fold difference. For VLS, there was a 2-fold difference between the lowest-reimbursing state, Maine ($92.20) and the highest, New York ($182.96). All US dollar values were uniformly adjusted for inflation to 2018 dollar values. Most DFLs in 2016 were performed by otolaryngologists (93.6%). CONCLUSIONS AND RELEVANCE: The DFL utilization rates remained stable compared with VLS in the Medicare population from 2000 to 2016. There was a decrease in both DFL and VLS payments per procedure in the same time period and also weak correlations between reimbursement and utilization. Practice patterns and reimbursement varied geographically across the United States, though VLS exhibited significantly higher variation than DFL at the state level.